Exploring the future of Russias economy and markets : towards sustainable economic development - Sergi, Bruno S. (Emerald Publishing Limited, 2018)
Rich in natural resources, straddling Europe and Asia, and home to markets of immense scale, Russia is an essential, critical player in an unprecedently complex global economy. Yet it has yet to fully exploit its unique position within this brave new world. Exploring the Future of Russia's Economy and Markets offers the first serious study of Russia's contemporary economic growth and economic aptitude. Based on the April 2017 conference "'New Reality' and Russian Markets" held at Harvard University and co-hosted by Harvard Davis Center for Russian and Eurasian Studies and RUDN University, Moscow, it brings together world-renowned thinkers to offer the latest empirical research on recent financial risks, institutional policies, and financial stability, all while weaving sound economic analyses around countercyclical expansionary macrotrends within the global market, current fiscal and monetary policies, and business cycles. It provides definitive technical insights into fintech, industrial policies and technological parks, TNCs, the oil and natural gas industry, and the impact of international sanctions on Russia's sustainable development. Cumulatively, the chapters gathered here demand that Russia look for alternative key drivers to get its economy going. The distinguished economists gathered here offer flexible bases for economic and financial stability that would foster sustainable economic development for Russia. Exploring the Future of Russia's Economy and Markets is essential reading for economists, policy makers, and students wishing to understand how Russia might take full advantage of its pivotal position within the world economy.